Metastatic Spinal Lesions: State-of-the-Art Treatment Options and Future Trends - Georgy, B.A. (American Journal of Neuroradiology, 2008)
SUMMARY: The purpose of this article is to review the current state of the art for treating symptomatic spinal fractures associated with malignant lesions and to present potential future trends in treatments for this patient population. Epidemiology, clinical presentation, and biomechanical ramifications of these lesions are summarized and treatment regimes, clinical outcomes, and complications and technical issues associated with treatments are presented. Potential future trends and new technologies for performing vertebral body augmentation in patients with metastatic spinal lesions are also discussed.